Impact of mitral valve anatomy suitability in echocardiographic and clinical evolution in patients referred for percutaneous edge-to-edge repair. (14th October 2021) - Salinas Gallegos, A; Pozo Osinalde, E; Gordillo, X; Jimenez Quevedo, P; Mahia, P; Marcos-Alberca, P; Tirado, G; Islas, F; Macaya, C; Perez-Villacastin, J; Fernandez-Ortiz, A; Nombela-Franco, L; et al.
Abstract: Background: Percutaneous edge-to-edge mitral repair has become an effective therapeutic alternative to surgery in high-risk patients with moderate-to-severe mitral regurgitation (MR). A traffic light system has been proposed to evaluate echocardiographic suitability for this therapy. However, few data is available regarding prognostic impact of these criteria. Purpose: To study the impact of imaging eligibility classification in echocardiographic and clinical evolution. Methods: We evaluated all the consecutive patients who underwent percutaneous mitral repair with the MitraClip system between 2010 and 2020 in our tertiary university hospital, excluding the redo procedures (n=1). Imaging eligibility classification was blindly made by two experts in structural heart disease. Pre and posprocedural echocardiographic measurements were reassessed and clinical events were collected from medical records. Results: 87 patients (65.5% males) with a mean age of 76±10 years were finally included. Regarding mitral valve disease, 13 (14.9%) was graded as moderate-to-severe whereas 74 (85.1%) was considered severe. MR etiology was: functional 44.8%, organic 34.5% and mixed 20.7%. Prior to the procedure the NYHA class was III or higher in 88.5% and LVEF was 44.4±15.4%. Eligibility criteria was: green (44, 50.6%), yellow (39, 44.8%) and red (4, 4.6%). The later patients, with theorical contraindication for the procedure, were excluded from analysis. Although less number of clips were needed in green morphology (1.14 vs 1.46; p=0.01), pulmonary vein flow improved more markedly (Table) in these patients. This resulted only in a slightly greater reduction in MR grade at 6 months (−2.5 vs −1.9; p=0.008). No differences were noted in follow up absolute MR grade or changes in ventricular volumes, LVEF or pulmonary artery systolic pressure. Moreover, there was no impact in MACE during the evolution. Conclusion: Excluding contraindicated group, no relevant echocardiographic or clinical impact was noted regarding eligibility criteria for percutaneous edge-to-edge mitral repair. Thus, suboptimal patients may equally benefit from this therapy even in moderate-volume centers. FUNDunding Acknowledgement: Type of funding sources: None.